2008
DOI: 10.1634/stemcells.2007-1041
|View full text |Cite
|
Sign up to set email alerts
|

Human Embryonic Stem Cells Have Enhanced Repair of Multiple Forms of DNA Damage

Abstract: Embryonic stem cells need to maintain genomic integrity so that they can retain the ability to differentiate into multiple cell types without propagating DNA errors. Previous studies have suggested that mechanisms of genome surveillance, including DNA repair, are superior in mouse embryonic stem cells compared with various differentiated murine cells. Using single-cell gel electrophoresis (comet assay) we found that human embryonic stem cells (BG01, I6) have more efficient repair of different types of DNA dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
183
4
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(202 citation statements)
references
References 51 publications
13
183
4
2
Order By: Relevance
“…It is imperative that they must be equipped with effective cellular defense mechanisms to deal with various cellular insults and to ensure normal growth and development. Indeed, recent studies suggested that stress defense in human ESCs is superior to that of differentiated cells as demonstrated by their DNA repair capacity [ 20 ], which is down-regulated during differentiation [ 21 ]. Nonetheless, when the damages reach the degree that is beyond repair, apoptotic cell death of ESCs may be a safeguard mechanism to avoid potential described for self-renewal and pluripotency analysis.…”
Section: Cell Viability Proliferation and Cell Cycle Analysismentioning
confidence: 99%
“…It is imperative that they must be equipped with effective cellular defense mechanisms to deal with various cellular insults and to ensure normal growth and development. Indeed, recent studies suggested that stress defense in human ESCs is superior to that of differentiated cells as demonstrated by their DNA repair capacity [ 20 ], which is down-regulated during differentiation [ 21 ]. Nonetheless, when the damages reach the degree that is beyond repair, apoptotic cell death of ESCs may be a safeguard mechanism to avoid potential described for self-renewal and pluripotency analysis.…”
Section: Cell Viability Proliferation and Cell Cycle Analysismentioning
confidence: 99%
“…Embryonic and adult stem cells have more robust DNA repair systems compared to progenitor and differentiated cells (Bracker et al, 2006;Maynard et al, 2008). However, aged stem cells have reduced capability to repair DNA lesions and as a result accumulate genetic and epigenetic mutations.…”
Section: Cancer Stem Cells and Chemotherapy Responsementioning
confidence: 99%
“…The most simple explanation for this low amount of 8-oxoG would be a more effective removal of 8-oxoG in ESCs. However, neither elevated OGG1 protein levels nor enhanced enzyme activity have been observed in ESCs (Maynard et al, 2008). Another principle that could be used by hESCs to efficiently remove 8-oxoG would be recognition of 8-oxoG and initiation of its removal by other glycosylases.…”
Section: Base Excision Repairmentioning
confidence: 99%
“…Since ESCs proliferate fast, they should produce a higher amount of ROS than differentiated cells, which should result in increased oxidation of bases and an increased amount of 8-oxoG, a damaged base that is normally removed from the DNA by the N-glycosylase/DNA lyase OGG1 (reviewed in: Boiteux & Radicella, 1999). In contrast to this expectation, very little 8-oxoG has been measured in undamaged hESCs (Maynard et al, 2008). The most simple explanation for this low amount of 8-oxoG would be a more effective removal of 8-oxoG in ESCs.…”
Section: Base Excision Repairmentioning
confidence: 99%